“Trust in God – But Tie Your Camel First” : The Economic Organization Of The Trans-Saharan Slave Trade Between The Fourteenth and Nineteenth Centuries.: The Economic Organization Of The Trans-Saharan Slave Trade Between The Fourteenth and Nineteenth Centuries. (2005) - Unknown
No abstract available